Neural processing of Spatial Information: What we know about Place cells and what they can tell us about Presence. - O'MARA, SHANE MICHAEL (MIT Press, 2006)
Brain processing of spatial information is a very prolific area of research in neuroscience. Since the discovery of place cells (PCs)(O'Keefe & Dostrovsky, "The hippocampus as a spatial map," Brain Research 34, 1971) researchers have tried to explain how these neurons integrate and process spatial and non-spatial information. Place cells are pyramidal neurons located in the hippocampus and parahippocampal region which fire with higher frequency when the animal is in a discrete area of space. Recently, PCs have been found in the human brain. The processing of spatial information and the creation of cognitive maps of the space is the result of the integration of multisensory external and internal information with the brain's own activity. In this article we review some of the most relevant properties of PCs and how this knowledge can be extended to the understanding of human processing of spatial information and to the generation of spatial presence.
PUBLISHED
Keywords: Brain; Spatial behaviour; Neurons